The Role of Cognitive Emotion Regulation Strategies and Behavioral Activator-Inhibitor Systems in Depression of Female Students - Mahnaz Aliakbari Dehkordi; Maryam Aliakbari; Marziye Zolfagharinezhad; Monirosadat Hosseini; Mahshad Balali (دست‌آوردهای روان‌شناختی, 2022)
Aim: This study aimed to investigate the role of cognitive emotion regulation strategies and behavioral activator-inhibitor systems in depression.Methods: The research method was descriptive correlational with 240 female undergraduate and graduate students of Shahrekord University (Western province of Iran) selected through a random sampling method. They answered Beck Depression Inventory, Granovsky’s Cognitive Emotion Regulation Questionnaire, and Carver and White’s Brain Systems Scale. The data were analyzed using SPSS 22. Results: The mean and standard deviation of each variable were calculated as descriptive statistics, and Pearson correlation was employed to evaluate the relationships of variables. The results showed a significant negative correlation between behavioral activator systems and depression, and a significant positive correlation between behavioral inhibitor systems and depression. In general, the behavioral activator-inhibitor systems predicted 33% of depression variance. In addition, there was a significant positive relationship between maladaptive strategies of cognitive emotion regulation and depression and a significant negative relationship between adaptive strategies of cognitive emotion regulation and depression.Conclusion: The results showed that among the maladaptive strategies of cognitive emotion regulation, the catastrophic component predicted about 29% of depression variance, and among the adaptive strategies of cognitive emotion regulation, the acceptance component predicted about 39% of depression variance. In general, the results of this study indicated that brain-behavioral systems and emotional cognitive regulation strategies had chief roles in predicting depression. Relying on the findings of this study, we can present a practical framework to explain the symptoms of depression and its treatment.